Pengaruh Dividen Policy, Firm Size, Asset Structure, Dan Liquidity Terhadap Debt Policy (Jurnal Paradigma Akuntansi, 2022)
This study aims to ascertain dividend policies, company size, asset structure, and liquidity against debt policies in manufacturing companies listed on the Indonesia Stock Exchange during 2017-2019. This sample was selected by purposive sampling method and data that have been valid are as many as 37 companies. The data processing technique uses multiple regression analysis assisted by using the Eviews program version 11. The results of this study indicate that liquidity has a significant influence on debt policy, and shows the ability to increase the ability of debt policy. The implication in this research is that the ability of the company to pay off debt will have an effect on the level of debt to the company.